EXAMINING THE DISCOURSE ANALYSIS ON THE SONG LYRIC ENTITLED “HEAL THE WORLD” BY MICHAEL JACKSON - Willy Cardo Hutajulu; Oscar Pardomuan Butarbutar; Jeremia Situmorang; Silvia Torong; Vistan Sebasty Situmeang; Herman Herman (Sean Institute, 2023)
This library research aimed at finding the three aspects of discourse analysis: contextual, grammatical, and lexical aspects of Michael Jackson’s song lyrics entitled “Heal The World”. After analysis, it can be found that the life experience and background of the songwriter and singer are closely related to the idea proposed within the song lyrics. Whereas, the result of the grammatical and lexical analysis gives a depiction of cohesion and coherence of the song discourse of “Heal The World “.the first element we see in lines (79), (80), (81), (82), (83), (84), (85), (86), (87), (88), and (89) is the first plural personal pronoun reference. There is the pronoun